Optical, Thermal and Mechanical Properties of Creatininium 5-Sulphosalicylate Organic Crystal for Optical Limiting Applications - Kalaiyarasi, S.; Ravisankar, V.; Manikandan, Chitrarasu; Kumar, C. Amirtha (Asian Journal of Chemistry, 2026)
A novel organic nonlinear optical single crystal of creatininium 5-sulphosalicylate (C5SS) was grown by slow evaporation. From FTIR analysis, the presence of various vibrational modes and functional groups in the synthesised material was confirmed. The thermal stability of grown crystal was analysed by TG-DSC analysis. UV-visible transmittance studies showed the transparency region, cut-off wavelength and band gap of the grown crystal. Laser tolerance of the grown crystal was estimated to be 5.23 GW cm–2. Microhardness studies were also performed on C5SS single crystal to reveal its mechanical properties. A Z-scan technique was employed to evaluate the nonlinear absorption coefficient, nonlinear refractive index and nonlinear optical susceptibility. The optical limiting behaviour of C5SS was observed at 28.14 mW input power.